Analysis of the Influence of Competence and Work Culture on Employee Performance with Moderation of Exit Intentions: A Case Study at Bank Syariah Indonesia - Anton Hindardjo; Muhammad Fikri Pratama; Juhary Ali (International Journal of Management Science and Application, 2022)
Employee performance is the result achieved by a worker within a certain period of time. This study aims to determine, analyze and identify how much of the factors that influence the performance of employees at Bank Syariah Indonesia, Depok city branch by mediating intention to leave or resign. The method used in this research is quantitative method. The results showed that based on the results of the questionnaire test showed that the questionnaire data presented had met the validity and reliability requirements of the data. Based on the results of the outer model test using the smart PLS 3.3 application, namely the Convergent validity, Discriminant validity, and Composite reliability tests. The inner model test results show that all these factors.